Comparative Evaluation of Bioactivity of Cention N Incorporated with Inorganic Nanoparticle: A Scanning Electron Microscope-Energy-Dispersive X-ray Spectroscope Analysis - Pokharkar, Pranjali Mahesh; Hadakar, Savita; Taur, Swapnil; Gaonkar, Namrata; Shashikiran, N. D.; Gugawad, Sachin; Waghmode, Sonali (Journal of the International Clinical Dental Research Organization, 2023)
ABSTRACT Context: Cention N, a new basic filling material, is a real alternative to amalgam and glass ionomer cement which offers characteristics and other advantages over both amalgams and glass ionomer. As the literature lacks studies of this newly launched material, we intended to study the addition of inorganic nanoparticles to Cention-N to improve its bioactivity. Aims: The objective of the study was to evaluate and compare the bioactivity of Cention-N incorporated with inorganic nanoparticles. Subjects and Methods: Niobium pentoxide (Nb2O5) nanoparticles and Cention N were the materials utilized (Nb2O5). In this investigation, 20 samples were used. Group 1 consisted of 10 samples of Cention N and Group 2 consisted of 10 samples of 3 wt% of Nb2O5 nanoparticles incorporated into Cention N. After application of the material, the samples were immersed in simulated body fluid and incubated at 37°C for 28 days. On the 29th day, the surface of the specimens was observed under scanning electron microscope (SEM) and energy-dispersive X-ray spectroscope (EDX). Statistical Analysis Used: All the statistical analyses will be performed using SPSS software version 17. This was followed by Tukey post hoc test for pairwise comparison. Results: SEM images of Group 2 revealed crystals in the apatite-like phase, while EDX analysis revealed an increase in the Ca and P content with 71.01 wt% and 35.56 wt%, respectively. As a result, the SEM-EDX analysis of Cention N after the addition of 3 wt% Nb2O5 nanoparticles revealed an enhancement in its bioactivity. Conclusion: The incorporation of Nb2O5 to Cention N can be used as an alternative and can be used for further in vivo testing.